Reliable deployment, reconfiguration, and control of cloud applications - Salaün, Gwen (My University, 2015)
Cloud applications consist of a set of interconnected software components distributed over several virtual machines. Setting up, (re)configuring, and monitoring these applications are difficult tasks, and involve complex management protocols. In this talk, I will first present two protocols for deploying and dynamically reconfiguring cloud applications, respectively. I will also present synthesis techniques for generating controllers in charge of coordinating autonomic managers and cloud applications. These approaches have been devised with the support of formal techniques and tools.
Keywords: Ingeniería del software